Explaining the gender wage gap in Georgia - Tamar Khitarishvili (Levy Economics Institute of Bard College, 2009)
This paper evaluates gender wage differentials in Georgia between 2000 and 2004. Using ordinary least squares, we find that the gender wage gap in Georgia is substantially higher than in other transition countries. Correcting for sample selection bias using the Heckman approach further increases the gender wage gap. The Blinder Oaxaca decomposition results suggest that most of the wage gap remains unexplained. The explained portion of the gap is almost entirely attributed to industrial variables. We find that the gender wage gap in Georgia diminished between 2000 and 2004.
Keywords: J16; J31; P20; 330; gender wage gap; economic transition; Georgia